1995
DOI: 10.1002/bjs.1800820738
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between pylorus-preserving and Whipple pancreatoduodenectomy

Abstract: Between 1989 and 1993, 62 patients underwent Whipple pancreatoduodenectomy and 75 pylorus-preserving pancreatoduodenectomy (PPPD); 35 patients in the first group and 37 in the second had pancreatic adenocarcinoma while 17 and 21 patients respectively had periampullary adenocarcinoma. The aim of this retrospective study was the comparison of operative outcome, nutritional recovery and survival of patients who underwent these two operations. No significant differences were found between the two groups in operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
67
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 21 publications
6
67
0
4
Order By: Relevance
“…However, the pylorus preservation seems to have advantages in the functional and nutritional status 3,8 . A longitudinal follow-up showed that differences in postoperative weight gain are correlated rather with resection margins and tumor recurrence than with the type of resection 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pylorus preservation seems to have advantages in the functional and nutritional status 3,8 . A longitudinal follow-up showed that differences in postoperative weight gain are correlated rather with resection margins and tumor recurrence than with the type of resection 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, several studies have been conducted to evaluate clinical and nutritional longterm effects after PD [3][4][5][6][7][8] . However, most studies have not made a complete nutritional assessment and they do not describe digestive complaints or details of food intake patterns.…”
Section: Introductionmentioning
confidence: 99%
“…4,[12][13][14][15][16][17][18][19] Although delayed gastric emptying is not associated with mortality, it can be a troublesome complication and can jeopardize nutritional status when patients do not receive enteral or parenteral nutrition. It also increases the postoperative hospital stay.…”
mentioning
confidence: 99%
“…13 Others have described delayed gastric emptying as gastric stasis requiring gastric suction for 7 days 18,19 or Ն10 days. 12,17 Pylorus-preserving pancreaticoduodenectomy (PPPD) is considered a good alternative to standard pancreaticoduodenectomy, or Whipple's procedure (PD). Most reports have shown similar survival for the two techniques, and PPPD is now generally accepted as an equally effective procedure for pancreatic or periampullary tumors.…”
mentioning
confidence: 99%
“…3,4,[9][10][11] A less serious complication is delayed gastric emptying, which is reported to occur at 25-70% after pancreaticoduodenectomy, with an average of 30%. 4,[12][13][14][15][16][17][18][19] Although delayed gastric emptying is not associated with mortality, it can be a troublesome complication and can jeopardize nutritional status when patients do not receive enteral or parenteral nutrition. It also increases the postoperative hospital stay.…”
mentioning
confidence: 99%